Simulation study of lead removal from waste water by using tea waste as biosorbent. - Baharuddin, Nurul Huda (Areadiscover, 2022)
Toxic heavy metals such as lead have been discharged into water streams due to industrialization, particularly from the stationery industry. Even though there are several ways to remove heavy metals, running the procedures is quite expensive. As a result, this research will simulate the performance of tea waste as a bio sorbent agent for removing lead ions from wastewater. The Fixed-Bed Adsorption Simulation Tool (FAST) program will create a simulation in this investigation. Furthermore, different manipulation factors such as lead ion initial concentration, contact time, and adsorbent dose were employed to evaluate its influence on the biosorption process. The results are comparable to a previous study on tea waste as a source of biosorption. According to the previous research and case study, the optimal contact duration is 60 minutes, the best metal ion concentration for adsorption is 100 mg/L, and the best adsorbent dose is 2 g. Furthermore, a comparison of the Langmuir isotherm with the Freundlich isotherm reveals that the Langmuir isotherm produces better results. Moreover, when the pseudo-first-order kinetic model is compared to the pseudo-second-order kinetic model, the pseudo-first-order yields superior results.